Asian Cities as Future Potential Financial Centers of the World - Jałowiecki, Marcin (Azjatyckie miasta jako nowe centrum finansowe świata, 2011)
The article describes key factors for future financial centers of the World. We describe the current financial centers of the world, which are divided into three areas like Europe, Asia, and North America. The article also presents what will happen in 15 years with the biggest financial centers of the world facing a creation of a new financial center of the world in China.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 192, s. 41-50
Keywords: growth factors; global financial centers; GDP; global capital market